2003
DOI: 10.1080/0141861031000071999
|View full text |Cite
|
Sign up to set email alerts
|

Undissociated screw dislocations in silicon: Calculations of core structure and energy

Abstract: The stability of the perfect screw dislocation in silicon has been investigated using both classical potentials and first principles calculations. Although a recent study stated that the stable screw was located both in the 'shuffle' and 'glide' sets of {111} planes (Koizumi et al, 2000, Phil. Mag. A, 80, 609), it is shown that this result depends on the classical potential used, and that the most stable configuration belongs to the 'shuffle' set only, in the centre of one ( 101) hexagon. We also investigated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
64
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 29 publications
5
64
0
Order By: Relevance
“…On the basis of geometrical arguments, it has been suggested that this mixed shuffle-glide configuration is a saddle point, and therefore, is not stable [28]. This has been confirmed for Si by first principles calculations [12]. Therefore, in this work, the B configuration is obtained by constraining the two atoms closest to the dislocation line to remain at the same distance along [101].…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…On the basis of geometrical arguments, it has been suggested that this mixed shuffle-glide configuration is a saddle point, and therefore, is not stable [28]. This has been confirmed for Si by first principles calculations [12]. Therefore, in this work, the B configuration is obtained by constraining the two atoms closest to the dislocation line to remain at the same distance along [101].…”
mentioning
confidence: 98%
“…So far, theoretical studies have shown that the non-dissociated screw belongs to the 'shuffle' set, though there has been a controversy about the most stable structure [11,12]. Other covalent materials with zinc-blende structure are expected to behave like silicon, at least at high temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if the considered dislocations are ideally straight and infinite, the core structure may be investigated with few hundreds of atoms. Precise electronic and atomic structure calculations can then be performed using ab initio methods [1,2,3,4,5]. Still, investigating the formation, mobility or interaction of dislocations requires a large system with a few thousands of atoms [6], preventing the use of such methods.…”
Section: Introductionmentioning
confidence: 99%
“…First, in this work we have favored a shuffle core for the screw dislocation [25], although it has been shown that a glide core is energetically more stable [26,27]. Our choice has been motivated by the fact that the glide core is necessarily reconstructed along the dislocation line, yielding a structure close to reconstructed partial dislocation cores.…”
mentioning
confidence: 99%